Money Matters Addressing the Financial Sustainability of Security Sector Reform - Keane, Rory (SSR Papers, 2015)
Although the financial sustainability of United Nations (UN) support to institutional capacity building in post-conflict contexts may be the least analysed topic on the peacebuilding agenda, understanding the costs of rebuilding and maintaining the security sector should be one of the most important priorities for security sector reform (SSR) practitioners today. Through innovative partnerships between the UN and the World Bank, a new and important practice area in public financial management of the security sector is beginning to take shape. This paper traces the new demands placed on peacekeeping operations to â get more bang for every peacekeeping buckâ , and explores how to match SSR priorities and recurring costs in the security sector with available resources over the long term. In presenting the lessons learned from the security sector public expenditure review conducted by the UN and the World Bank in Liberia in 2012, the first such review jointly undertaken by the two organizations, the paper seeks to illustrate how the discussion on right-sizing of the security sector can go hand in hand with a discussion on right-financing in order to help prioritize key reforms pragmatically in light of the available fiscal space. Specifically, the paper provides SSR practitioners with insights into the challenges often encountered when assisting national authorities to address the political economy of SSR, and how to navigate those dilemmas.